2016
DOI: 10.1177/1591019916653257
|View full text |Cite
|
Sign up to set email alerts
|

Stent retriever thrombectomy with aneurysm in target vessel: Technical note

Abstract: Aneurysms within large occluded target vessels can present significant challenges for neuro interventionists because rupture can be catastrophic. We recently encountered a case of left internal carotid artery–middle cerebral artery (MCA) ischemic stroke with an incidental MCA bifurcation aneurysm that we were already aware of. IV tissue plasminogen activator (tPA) with mechanical thrombectomy (MTE) was performed with a stent retriever, proximal to the aneurysm. TICI 2b recanalization was achieved. MTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…The present case report supports this clinical maneuver in patients with large vessel occlusions thereby offering the possibility of a good functional recovery [3]. This procedure was performed to avoid the rupture of the aneurysm caused by the traditional thrombectomy with a stent retriever [6][7][8]. Even though aspiration thrombectomy might be safer than thrombectomy with stent retriever in an ipsilateral unruptured intracranial aneurysm, the evidence is lacking and there are no studies available comparing these two techniques.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The present case report supports this clinical maneuver in patients with large vessel occlusions thereby offering the possibility of a good functional recovery [3]. This procedure was performed to avoid the rupture of the aneurysm caused by the traditional thrombectomy with a stent retriever [6][7][8]. Even though aspiration thrombectomy might be safer than thrombectomy with stent retriever in an ipsilateral unruptured intracranial aneurysm, the evidence is lacking and there are no studies available comparing these two techniques.…”
Section: Discussionsupporting
confidence: 56%
“…Here we show the safety and efficacy of a primary direct aspiration of a thrombus in a patient with a concomitant partially non-ruptured thrombosed aneurysm in the same blood vessel, in this case the right MCA. It should be noted though that the rupture of an aneurysm during thrombectomy is a lifethreatening complication, which should not deprive these patients of these procedures, but rather a particularly cautious approach may be justified [6][7][8]. The present case report supports this clinical maneuver in patients with large vessel occlusions thereby offering the possibility of a good functional recovery [3].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In such cases, careful wire manipulation and fluoroscopic monitoring are necessary in advancing a device to the distal side of the occluded vessel. 10,11) Although Penumbra systems 10,11) and stent retrievers 12) have been used for mechanical thrombectomy in AIS patients harboring cerebral aneurysms, in cases of a hidden aneurysms the former appears safer because there is no need to pass the site of occlusion. Antithrombotic therapy for thrombosed cerebral aneurysms complicated by AIS has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…1,2) Although such condition is relatively rare, it is commonly recognized and there have been several case series or case reports in which an intra-aneurysmal thrombus caused embolism of the distal cerebral artery, as demonstrated in the present case, or growth of an intra-aneurysmal thrombus led to occlusion of the parent artery. 1,2,[5][6][7][8][9][10][11][12] Several studies reported that the administration of alteplase to AIS patients harboring unruptured cerebral aneurysms did not increase the risk of hemorrhage from the aneurysms or symptomatic intracranial hemorrhage. [13][14][15][16] Therefore, administration of alteplase to AIS patients should not be hesitated for the presence of cerebral aneurysm alone.…”
Section: Discussionmentioning
confidence: 99%